Information technology in a global business environment : readings and cases - Deans, Candace. (Boyd and Fraser, 1996)
This book is about: Globalization of the marketplace; Globalization of the organization; Global information systems and technology: Planning and strategic implications; Global connectivity and telecommunications; Management of global information flows; Integrating technology, systems, and people across the globe; and Selected cases.